ChemInform Abstract: Development of a Mild and Versatile Directed Cycloaddition Approach to Pyridines. Issue 13 (March 2015) - Bachollet, Sylvestre P. J. T.; Vivat, Jerome F.; Cocker, Dean C.; Adams, Harry; Harrity, Joseph P. A.
Abstract A Lewis base directed cycloaddition of triazines with alkynylboranes allows the regioselective approach to highly substituted pyridine structures including bipyridines.